Relevance Weighting of Tier 1 Endocrine Screening Endpoints by Rank Order. (7th February 2014) - Borgert, Christopher J.; Stuchal, Leah D.; Mihaich, Ellen M.; Becker, Richard A.; Bentley, Karin S.; Brausch, John M.; Coady, Katie; Geter, David R.; Gordon, Elliot; Guiney, Patrick D.; Hess, Frederick; Holmes, Catherine M.; et al.
<x xml:space="preserve">Abstract</x> Weight of evidence (WoE) approaches are recommended for interpreting various toxicological data, but few systematic and transparent procedures exist. A hypothesis‐based WoE framework was recently published focusing on the U.S. EPA's Tier 1 Endocrine Screening Battery (ESB) as an example. The framework recommends weighting each experimental endpoint according to its relevance for deciding eight hypotheses addressed by the ESB. Here we present detailed rationale for weighting the ESB endpoints according to three rank ordered categories and an interpretive process for using the rankings to reach WoE determinations. Rank 1 was assigned to in vivo endpoints that characterize the fundamental physiological actions for androgen, estrogen, and thyroid activities. Rank 1 endpoints are specific and sensitive for the hypothesis, interpretable without ancillary data, and rarely confounded by artifacts or nonspecific activity. Rank 2 endpoints are specific and interpretable for the hypothesis but less informative than Rank 1, often due to oversensitivity, inclusion of narrowly context‐dependent components of the hormonal system (e.g., in vitro endpoints), or confounding by nonspecific activity. Rank 3 endpoints are relevant for the hypothesis but only corroborative of Ranks 1 and 2 endpoints. Rank 3 includes many apical in vivo endpoints that can be affected by systemic toxicity and nonhormonal activity. Although these relevance weight rankings (WREL) necessarily involve professional judgment, their a priori derivation enhances transparency and renders WoE determinations amenable to methodological scrutiny according to basic scientific premises, characteristics that cannot be assured by processes in which the rationale for decisions is provided post hoc.